A nanomolecular approach to decrease adhesion of biofouling-producing bacteria to graphene-coated material. Issue 1 (December 2015) - Parra, Carolina; Dorta, Fernando; Jimenez, Edra; Henríquez, Ricardo; Ramírez, Cristian; Rojas, Rodrigo; Villalobos, Patricio
Abstract Background Biofouling, the colonization of artificial and natural surfaces by unwanted microorganisms, has an important economic impact on a wide range of industries. Low cost antifouling strategies are typically based on biocides which exhibit a negative environmental impact, affecting surrounding organisms related and not related to biofouling. Considering that the critical processes resulting in biofouling occur in the nanoscale/microscale dimensions, in this work we present a bionanotechnological approach to reduce adhesion of biofilm-producing bacteriaHalomonas spp. CAM2 by introducing single layer graphene coatings. The use of this nanomaterial has been poorly explored for antifouling application. Results Our study revealed that graphene coatings modify material surface energy and electrostatic interaction between material and bacteria. Such nanoscale surface modification determine an important reduction over resulting bacterial adhesion and reduces the expression levels of genes related to adhesion when bacteria are in contact with graphene-coated material. Conclusions Our results demonstrate that graphene coatings reduce considerably adhesion and expression levels of adhesion genes of biofilm-producing bacteriaHalomonas spp. CAM2. Hydrophobic-hydrophilic interaction and repulsive electrostatic force dominate the interactions betweenHalomonas spp. CAM2 and material surface in saline media, impacting the final adhesion process. In addition no bactericide effect of graphene coatings was observed. The effect over biofilm formation is localized right at coated surface, in contrast to other antifouling techniques currently used, such as biocides.